The Benefits of Using a Small Caliber Ureteroscope in Evaluation and Management of Urethral Stricture - Walid Shahrour; Pankaj Joshi; Craig B. Hunter; Vikram S. Batra; Hazem Elmansy; Sandesh Surana; Sanjay Kulkarni (Advances in Urology)
Introduction and Objective. The proper evaluation of urethral strictures is an essential part of the surgical planning in urethral reconstruction. The proper evaluation of the stricture can be challenging in certain situations, especially when the meatus is involved. We propose that the use of a small caliber ureteroscope (4.5 Fr and 6.5 Fr) can offer additional help and use for the surgical planning in urethroplasty. Methods. We prospectively collected data on 76 patients who underwent urethroplasties in Kulkarni Reconstructive Urology Center, Pune, India and Thunder Bay Regional Health Sciences Center, Thunder Bay, Canada. Patients had retrograde and micturition urethrograms performed preoperatively. The stricture was assessed visually using a 6.5 Fr ureteroscope. If the stricture was smaller than 6.5 Fr, we attempted using the 4.5 Fr ureteroscope. In nonobliterated strictures, we attempted bypassing the stricture making sure not to dilate the stricture. A glide wire would be passed to the bladder under vision. Stricture length, tissue quality, presence of other proximal strictures, false passages, and bladder tumors or stones would be assessed visually. If the penile stricture was near obliterative (smaller than 4.5 Fr caliber), a two-staged procedure is elected to be performed. For proximal bulbar strictures, if the urethral caliber is less than 4.5 Fr and the stricture length is less than 1 cm, we perform a nontransecting anastomotic urethroplasty (NTAU). If the stricture length is >1 cm, we perform a double-face augmented urethroplasty (DFAU). If the urethral caliber is >4.5 Fr and particularly those who are sexually active, ventral inlay with buccal mucosal grafts (BMGs) is performed. In mid to distal bulbar strictures, if the urethral caliber is >4.5 Fr, our procedure of choice is dorsal onlay with BMG. For those with urethral caliber <4.5 Fr and a stricture less than 1 cm, we perform a NTAU. For strictures longer than 1 cm, we perform a DFAU. With the exception of trauma, we very rarely transect the urethra. For panurethral strictures, we almost exclusively perform Kulkarni one-sided dissection. Results. Urethroscopy was performed in 76 patients who presented for urethroplasty from July 2014 to September 2014 (in Pune) and between April 2016 and September 2017 (in Thunder Bay). Bypassing the stricture was achieved in 68 patients (89%) while it was unsuccessful in 8 patients (11%). In all unsuccessful urethroscopies, the stricture was near obliterative <4.5 Fr. Our surgical planning changed in (13) 17% of the cases. Out of 43 bulbar strictures, the decision was changed in (9) 21% where we performed 4 DFAU, 3 AAU (augmented anastomotic urethroplasty), and 2 EAU (end anastomotic urethroplasty). In 13 penile strictures, we opted for staged urethroplasty including 3 Johansons and 1 first-stage Asopa in 30.7%. In 20 panurethral urethroplasties, 1 patient (5%) had a urethral stone found in a proximal portion of the bulbar urethra distal to a stricture ring that was removed using an endoscopic grasper. Conclusion. The use of the small caliber ureteroscope can help in evaluation of the stricture caliber, length, and tissue quality. The scope can also aid in placing a guide wire, evaluating the posterior urethra, and screening for urethral or bladder stones. It can also improve the preoperative patient counselling and avoid unwanted surprises.